The redefinition of the social-democratic agenda between the oil crisis and the end of real socialism (1973-1992) - Pedrosa, Fernando (Colección, 2017)
The aim of this paper is to show the strategies of social democratic organizations face new challenges that emerged in 1973 from the oil crisis and the emergence of so-called “post-materialist values”. It explores in depth one of the main strategies: The increase in transnational political activity and the creation of committees working on aspects related to development, security, nuclear arms race and the environment. These committees not only constituted a major turnaround from earlier traditions, also significantly influenced the subsequent developments in these areas.